On the Place of an Adverb in the Semantic Structure of the Sentence (the Adverb “тяжело”) - Лассан, Э. (Kalbotyra, 1980)
The article deals with the study of adverbs.The statement is made that adverbs express the property which can belong both to an action and to a thing. The analysis of adverbs was proceeded by the distinguishing sentences having different types of semantic structure. Depending upon the type or semantic structure, the property of the adverb is attributed to the substance or to the action.